Ranavirus in an outbreak of dermatophilosis in captive inland bearded dragons (Pogona vitticeps). Issue 2 (11th January 2016) - Tamukai, Kenichi; Tokiwa, Toshihiro; Kobayashi, Hideki; Une, Yumi
Abstract : Background: Various pathogens cause skin diseases in lizards. An outbreak of skin disease occurred in a population of 100 inland bearded dragons at a breeding facility in Japan; 50 developed skin lesions and 15 mortalities were reported. Hypothesis/Objectives: To identify the pathogens responsible for the skin lesions and to determine the cause of death. Animals: Eight specimens (three dead, two euthanized, three living) were randomly selected from a group of inland bearded dragons with skin lesions consisting of multifocal superficial dermatitis. Methods: Biopsy samples were taken from skin lesions and healthy skin of the live specimens. Postmortem examinations were performed on the dead and euthanized specimens. Skin samples were processed for microbiological culture, 16S ribosomal DNA (rDNA) sequencing for bacteria, ranavirus major capsid protein (MCP) gene sequencing and histopathological examination. Histopathological examinations were also performed on postmortem tissue samples. Results: Both Austwickia chelonae and ranavirus (DNA) were detected in the skin lesions. Pathological examination revealed no significant visceral lesions caused by A. chelonae or ranavirus infection in dead specimens. Conclusions and clinical importance: To the best of the authors' knowledge this is the first report of dermatophilosis due to A. chelonae infection in lizards and the first description of a concurrent infection with a ranavirus. The combined infection associated with the skin lesions may have been the primary cause of death. Co‐infection with a ranavirus should be considered as a possible factor in cases of reptilian dermatophilosis. Abstract : Background ‐ Various pathogens cause skin diseases in lizards. An outbreak of skin disease occurred in a population of 100 inland bearded dragons at a breeding facility in Japan; 50 developed skin lesions and 15 mortalities were reported.Hypothesis/Objectives ‐To identify the pathogens responsible for the skin lesions and to determine the cause of death.Conclusions and clinical importance ‐To the best of the authors' knowledge this is the first report of dermatophilosis due to A. chelonae infection in lizards and the first description of a concurrent infection with a ranavirus. The combined infection associated with the skin lesions may have been the primary cause of death. Co‐infection with a ranavirus should be considered as a possible factor in cases of reptilian dermatophilosis.